Expectations, Problems and Solutions for Postgraduate Academic Advisory in Study of Primary School Teacher Education - Sayım Aktay; Esadiye Pekdemir (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The aim of this research is to reveal the status of academic advising in graduate education in the field of classroom teaching. In this regard, it aims to examine the perceptions of academics and graduate students regarding the phenomenon of academic advising, their expectations from academic advising, the problems they encounter during the academic advising process, and their proposed solutions to these problems. In line with these objectives, a qualitative research approach was adopted in the study. Phenomenology, which is one of the qualitative research types, was used as the research model. The sample of the study consists of thesis-based master's students, doctoral students, and academics who provide academic advising in the graduate education programs of Akdeniz University, Anadolu University, Afyon Kocatepe University, Gazi University, Muğla Sıtkı Koçman University, Pamukkale University, Dokuz Eylül University, and Ege University in the 2020-2021 academic year. According to the findings of the study regarding the perceptions of graduate education academic advising, it was observed that both academics and graduate students have a positive perception of the phenomenon of academic advising. Furthermore, both academics and graduate students generally define academic advising as a guidance process. Regarding the expectations related to graduate education academic advising, it was found that both academics and g raduate students have various expectations from academic advising. Regarding the problems encountered in graduate education academic advising, the findings reveal that academics face difficulties mainly due to the students' deficiencies in scientific research skills and scientific research methods during the thesis stage. On the other hand, graduate students face problems in the academic advising process, particularly in terms of academics not providing timely feedback, inadequate guidance in research methods, and working with an advisor they did not choose. Additionally, it emerged that the main problem for graduate students in the field of classroom teaching is the difficulty in finding academics specialized in their field. The findings regarding the proposed solutions to the problems in graduate education academic advising indicate that academics mainly emphasize two topics in their proposed solutions. Firstly, it is suggested that especially master's students should go through a one-year preparation process, such as scientific preparation, before starting their master's courses. Secondly, it is recommended that academics who will provide academic advising should undergo a specific education on "academic advising" and a framework should be established for academic advising. When examining the proposed solutions from the perspective of graduate students, it is seen that the most commonly expressed solution is the ability to choose the individuals who will provide them with academic advising throughout their graduate education.